DAKWAH MOVEMENT ON PSYCHOLOGICAL PARADIGM - Abdul Hamid (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Mankind as mad’u or target da’wah consists of the soul and the body. Since da'wah intends to change person’s psychological attitudes, knowledge of the psychology of da'wah becomes a very important thing. This paper is in the form of a literature review that discusses the theoretical movement of psychological da’wah, the importance role of psychological da'wah, the basis of psychological da'wah, and the elements of psychological da'wah. This study applies qualitative method with descriptive approach. The aims of this study are to describe and interpret da'wah on psychological paradigm in a descriptive narrative manner. Social da'wah paradigm can be defined as a fundamental view, framework or basis of thinking that is used in understanding the basic concepts in exploring a science that discusses psychology which is reflected in a human behavior and its relation to the environment as an effort to invite, encourage, call, and convey to the community in the form of solicitation of goodness and prevention of evil according to Islamic principle. The urgency of the psychological paradigm emphasize that da'i demanded control about the human psyche as individuals and members of groups. The essence of da'wah actually lies in efforts to prevent community from psychological problems by inviting, motivating and guiding individuals to be healthy and prosperous in body and soul, so that they can receive the message of da'wah and can carry out religious teachings in accordance with the demands of religious law. There are several elements of the psychological da'wah that must be considered, namely the message of da’wah, psychology of the da'i and mad'u (the target of da’wah). The psychological basis of da'wah includes the personality of the da'I who is seen as good in society, da'wah messages that are communicative and adapted to the classification of attitudes as well as psychological condition of mad'u (the target da’wah).